Comportamento e conhecimento sobre doenças sexualmente transmissíveis em população com 50 anos e mais de idade - Olivi, Magali (2006)
The objective of the present study is to describe the sexual behavior and knowledgement about STD/aids in fifty years and older population in Cuiabá city. The sexually transmitted diseases (STD) are among the most common problems of public health around the world. In Brazil, Aids epidemic, were showed in four distinct moments marked by majority infection among homosexual and heterosexual male population; by an increment of drug addicted persons category, youthfully and heterosexualization of the epidemic; by an increase of transmition among female population and consequent vertical transmition and by the presentday epidemic with an increase of Aids cases in up to fifty years old people. Self-aplicated questionnaire answered by 165 employees of Health State Departament of Cuiabá - MT. Calculation of the sample size was used Statistica 6.0 program and to the statistics analysis of samples was used QUI quadrado test with a rate of 5% beyond the logistical regression analysis. Most of employees are female (61%); 45% have a higher education and 44.4% have an income of 1 to 5 minimum wage. As for sexual behavior 62.4% state having a permanent partner; men take condoms 1.6 more times than women and have sex 1.7 more times thanwoman; 83.1% did not wear condom the last time they had sex. As for knowledge, a hundred percent know what STD are; 88% of the women and 93 % of the men stated that condom prevent from STD/aids e 54.6 % of the women and 50.8 % of the men found possible to get STD. As a result of logistical regression analysis showed that multivaried analysis of variable of behavior associated to the perception to get STD/aids showed that the ones that did not wear condoms the last time they had sex were the ones with better perception as for the risk to get STD/aids, and in the multivaried analysis of variable of knowledge associated to the perception to get STD/aids shows that the fact of having answered that anyone can get STD/aids, they also see themselves as vulnerable. The results show that the knowledgement about STD/aids does not change the behavior as for the use of condom while having sex.